Modification of NaCl structure as a sodium reduction strategy in meat products: An overview - Rios-Mera, Juan D. (2021)
Sodium chloride (NaCl) is an indispensable ingredient in meat products, but the consumption of high doses of sodium contained in their formulations may bring about negative health implications. The replacement of NaCl by other salts in meat products has been a technological challenge. Accordingly, this review highlights the importance of NaCl over other sodium and non‑sodium salts in the saltiness perception and proposes the use of reduced-size and shapes of NaCl to maximize saltiness perception, while using less NaCl dosages in meat products. However, the effect of matrix components (water, proteins and fats) on the final salty taste is of special consideration. To counteract the effect of the matrix components, two main routes of incorporation of different NaCl types in meat products are discussed: encapsulation and protection of NaCl by the hydrophobic component of the meat product. Given the limited number of publications using this potential strategy, more studies on the application of these technological strategies are required. © 2020 Elsevier Ltd